CALM: Cultivating Awareness, Learning, and Mastery to Reduce Anger and Violence Through Combat Sports - Andrew M. Lane (Youth)
Youth violence is a pressing social issue. Many well-informed interventions to reduce youth violence fail due to low uptake. Combat sports—such as boxing, judo, and mixed martial arts—appear to encourage aggression, making them appealing to individuals prone to violent behavior. However, rather than reinforcing violence, these sports instill discipline, goal-directed behavior, and self-control. This paper argues that combat sports align with the values of at-risk youth, increasing their participation, while simultaneously teaching them emotional regulation and resilience. I propose that structured combat training provides a sustainable intervention by fostering self-awareness, cognitive control, and respect within a rule-governed environment. Furthermore, training combat instructors in emotion regulation strategies could enhance these benefits. By providing motivation, capability, and opportunity, combat sports present a viable pathway to reducing violent behavior among youth.